Indeks Maya dan Indeks Entomologi Vektor Demam Berdarah Dengue di Kabupaten Mamuju Tengah, Sulawesi Barat - Murni Murni; Nelfita Nelfita; Risti Risti; Hasrida Mustafa; Malonda Maksud (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
The existence of containers as a potential habitat breeding places for mosquitoes in the community can affect the population density of Aedes. The maya index is an indicator to measure the number of containers that can be a breeding places for mosquitoes. This study aims to determine maya index and entomology index in Central Mamuju Regency, West Sulawesi Province. This study was an observational study conducted in 2015 in three sub-districts (Topoyo, Tappilina, and Karossa) in Central Mamuju Regency. Data collection through structured interviews with household heads in 100 randomly selected houses using the closest house method and measuring larvae density using the single larva method. The results showed that the Breeding Risk Index (BRI) for the three sub-districts in Central Mamuju Regency are mostly in the medium category, while Hygiene Risk Index (HRI) and Maya Index (MI) are in a low category. Based on House Index (HI) and Container Index (CI) indicators means have a moderate risk of transmission Dengue.